Climate Change and Climate Induced Migration in Pakistan: A Threat to Human Security (The Study of RajanPur and Taunsa Sharif after Flood 2022) - Hashmi, Rehana Saeed (Annals of Human and Social Sciences, 2023)
Climate change is expeditiously reshaping the socio-geographic landscape of Pakistan and thus has compelled the communities to adapt to the unrivaled environmental challenges. The unprecedented climate change has raised concerns regarding human security in Pakistan. The background of this study is related to the massive damage of infrastructure and human loss during and after flood 2022 in the areas of Southern Punjab (RajanPur and Taunsa Sharif). The principal objective of the study is to understand the hazardous impact of the trilogy of climate change, climate-induced migration, and human security. By analyzing the intersecting factors such as water scarcity, damaged livelihoods, lack of shelter, security concerns, agricultural shifts, and extreme weather events of 2022, the article highlights significant problems of the flood affected population. A mixed method approach has been opted for conducting the research, i.e., qualitative methodology has been used for developing a theoretical understanding of climate change, climate-induced migration, and human security. Moreover, quantitative methods such as surveys have been conducted in the affected regions. The mixed method research design has been operationalized following a case study approach. The study suggests that a comprehensive approach is imperative to safeguard human security in Pakistan.